The effect of steam generator tube plugging on its overall thermal performance - A Systems CFD-Based Study - Ntuli, Japhet Mkhipheni Ali (Department of Electrical Engineering, 2020)
The steam generator in a pressurized water reactor power plant acts as a fission product barrier between primary and secondary system. Material failure of the tube bundle barrier could therefore lead to a release of radioactive product into the secondary side. Several repair methods have been used to address tube leakage, with the most popular being tube plugging. The objective of this study was to quantify the effect of tube plugging on the thermal performance of a steam generator. For this purpose, the systems computational fluid dynamics (CFD) software Flownex® was used. First, a Flownex® model of the steam generator was developed and validated via comparison of the results to a validated model from the literature. Following this, a hydro-thermal analysis was performed to determine the effect of the tube plugging on the thermal performance under normal operational conditions (excluding the possibility of a tube rupture). Tube plugging of up to 20% was investigated. The model predicted the following effects: decrease in heat transfer, primary coolant mass flowrate and primary outlet pressure. Further, primary flow velocity, pressure drop and outlet temperature increase with increasing tube plugging. On the secondary side, tube plugging lowers the mixture quality in the boiling region and steam production while the re-circulation ratio was increased. Lastly, the model predicted a plugging ratio limit of 17.3%. Beyond this point, the steam generator does not extract sufficient heat from the reactor at 100% power.